Reorientasi Program Profesi Psikologi - Justin, Ernest; Supratiknya, Augustinus (Fakultas Psikologi Universitas Sanata Dharma, 2023)
Law number 23 of 2022 concerning “psychology education and services” provides certainty regarding higher education of psychology in Indonesia. In particular, this article wants to explore and provide orientation towards professional psychology education programs in Indonesia. After discussing the brief history of professional psychology education programs in Indonesia and the legal complexities that accompany them, the authors explore the curriculum of professional programs compared to academic programs. The writers try to look at two aspects of the curriculum: (1) substantive knowledge and skills regarding scientific disciplines; (2) knowledge of the service context and practice of the discipline. The authors then try to identify four competencies that need to be learned in the Professional Psychology program. These competencies will be described in the curriculum framework proposed by the authors; the curriculum framework emphasizes practical aspects, competency-based curricula, and problem-based learning.